Epidemiology and Management of Seasonal Influenza Outbreaks in Long-Term Care Facilities in the Health Service Executive East Area of Ireland During the 2013-2014 Influenza Season. - L., O’Connor; H., Murphy; E., Montague; M., Boland (Journal of Immunization, 2017)
We describe seasonal influenza-like illness (ILI) outbreaks in long-term care facilities in the Health Service Executive (HSE) East area of Ireland in the 2013/2014 influenza season, risk factors associated with outbreak duration and attack rates, and management challenges. Separate questionnaires were distributed to 28 facilities who reported an outbreak and to public health specialists leading outbreak management, with a 79% response rate. Mean outbreak duration (21 vs 17 days; p=0.046) was longer in facilities with staff vaccination rates of <40%. Facilities with a high attack rate (≥50%) were less likely to have an outbreak plan (p=0.03). Smaller facilities (under 50 residents) had a higher attack rate (50% vs 23%, p=0.003) even when controlled for staff vaccination rate (p=0.01). Prior to the outbreak, resident vaccination rates were high (82%, above the World Health Organization target of 75%) but staff vaccination rates were low (39%). Reported challenges to ILI outbreak management in long term care facilities included visitor restrictions, staff education issues, outbreak notification delays and lack of outbreak lead in facilities. Targeted public health-assisted planning, training and response, comprising of staff vaccination, education, written policies, with early notification and prompt response would facilitate a more co-ordinated approach to the management of outbreaks, and reduction in infection rates and consequent morbidity.